Pengaruh Lingkungan Kerja terhadap Kualitas Pelayanan pada Dinas Tenaga Kerja dan Perindustrian Kota Padang - Irdiyanti Irdiyanti; Syamsir Syamsir (Faculty of Social Science, Universitas Negeri Padang, 2018)
This research aimed to determine the influence of work environment on service quality at Labor and Industry Agency of Padang City. This was an associative study with a causal relationship variable. The population of this study was all of people who received services at Labor and Industry Agency of Padang City on July 2018. Sample of this research consisted 265 respondents, determined through the table of Isaac and Michael with a level of 10% error. Data in this research were collected through questionnaires and analyzed with Multiple Linear Regression Analysis by SPSS version 22.0 software. The results of this research showed that there was a significant influence of physical work environment (X1) on service quality (Y) with a contribution amounted to 22.3%. Then, there was also a significant influence of non-physical work environment (X2) on service quality (Y) with a contribution amounted to 8.9%. Furthermore, there was also co-significant influence on the physical work environment (X1) and the non-physical work environment (X2) simultaneously on service quality (Y) with a contribution as many as 25.8%.